2018
DOI: 10.1111/acem.13432
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician Interpretation of Point‐of‐care Ultrasound for Identifying and Grading of Hydronephrosis in Renal Colic Compared With Consensus Interpretation by Emergency Radiologists

Abstract: Emergency physicians were found to have moderate to high sensitivity for identifying hydronephrosis on POCUS when compared with the consensus interpretation of the same studies by emergency radiologists. These POCUS findings by EPs produced more definitive results when at least moderate degree of hydronephrosis was present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Third, although the CT or MRI images showed that all patients had renal pelvis or calyx dilation with proximal ureteral dilatation, we could not review the ultrasound images because our hospital does not retain ultrasound images. A previous study demonstrated that ultrasound and CT scans had different sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio for the diagnosis of hydronephrosis (31). This might be a limitation because some patients were diagnosed only by ultrasound.…”
Section: Discussionmentioning
confidence: 98%
“…Third, although the CT or MRI images showed that all patients had renal pelvis or calyx dilation with proximal ureteral dilatation, we could not review the ultrasound images because our hospital does not retain ultrasound images. A previous study demonstrated that ultrasound and CT scans had different sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio for the diagnosis of hydronephrosis (31). This might be a limitation because some patients were diagnosed only by ultrasound.…”
Section: Discussionmentioning
confidence: 98%
“…Moderate hydronephrosis was defined as the blunting or rounding of the calices or the obliteration of renal papillae without affecting the cortical thickness. Severe hydronephrosis was considered to be present if caliceal ballooning and cortical thinning were found [ 14 ]. We also collected data on stone location (calculus at the junction of the renal pelvis, multiple renal pelvis stones), operation time (>60 min, ≤60 min), intraoperative bleeding (>100 ml, ≤100 ml), intraoperative perfusion pressure (≤30 mmHg, >30 mmHg), and pyonephrosis.…”
Section: Methodsmentioning
confidence: 99%
“…104 In addition, bedside abdominal ultrasound can be used to evaluate, quantify, and guide paracentesis for abdominal ascites. 6 POCUS also has been used to diagnose obstructive nephropathy, 6 hydronephrosis, 105 nephrolithiasis, 106 and bladder distention, 107 as well as assisting in difficult Foley catheter placement. 108 All of these attributes make abdominal ultrasound ideally suited for routine use in the ICU.…”
Section: Pocus In the Critical Care Settingmentioning
confidence: 99%